Kepimpinan JKKK: Peranan ke arah kesejahteraan desa - Brahim, Malike; Yusuf, Sarina; Mohamad, Musliza (2014)
Well-being is not only referring to the aspect of health and safety, but it brought to a vey wide view, including the question of prosperity to the socio-economic and community development of the local people.In this issue, as the village-level organisation, the Village Development and Safety Committee (VDSC) had a very important role to bring the development and advancement to the people in terms of economy, infrastructure, cultural, religious, and so on.For this purpose, the YDSC's leadership plays an important role as the main agent to ensure the government's development programmes being beimplemented effectively and to achieve its goals in improving people's living standard.Therefore, the quality of VSDC leadership should be enhanced to ensure that it remains as a relevant role in formulating the people S well-being and free from the shadows of partisan politics.